Prediction and assessment of the effects of mixtures of four xenoestrogens. - Payne, J (2000)
The assessment of mixture effects of estrogenic agents is regarded as an issue of high priority by many governmental agencies and expert decision-making bodies all over the world. However, the few mixture studies published so far have suffered from conceptual and experimental problems and are considered to be inconclusive. Here, we report the results of assessments of two-, three- and four-component mixtures of o,p'-DDT, genistein, 4-nonylphenol, and 4-n-octylphenol, all compounds with well-documented estrogenic activity. Extensive concentration-response analyses with the single agents were carried out using a recombinant yeast screen (yeast estrogen screen, YES). Based on the activity of the single agents in the YES assay we calculated predictions of entire concentration-response curves for mixtures of our chosen test agents assuming additive combination effects. For this purpose we employed the models of concentration addition and independent action, both well-established models for the calculation of mixture effects. Experimental concentration-response analyses revealed good agreement between predicted and observed mixture effects in all cases. Our results show that the combined effect of o,p'-DDT, genistein, 4-nonylphenol, and 4-n-octylphenol in the YES assay does not deviate from expected additivity. We consider both reference models as useful tools for the assessment of combination effects of multiple mixtures of xenoestrogens.